Pertumbuhan Dan Produksi Kacang Tanah (Arachis hypogaea L.) Dengan Pemberian Pupuk Kandang Sapi Dan Pupuk Fosfat - Pendi Kurniawan Pasaribu; Asil Barus; Mariati Mariati (Universitas Sumatera Utara, 2014)
This research was aimed to know the effect of cow manure and phosphate fertilizer toward growthand production of peanuts. The research was conducted at the farm field with altitude ± 25 metersabove sea level, began from January until March 2012 using Randomized Block Design with twofactors. The first factor was cow manure which consist of four levels, that were K0 (0 g/plot), K1(875 g/plot), K2 (1.750 g/plot), and K3 (2.625 g/plot), and the second was phosphate fertilizerconsist of three levels, that were P0 (0 g/plot), P1 (17,5 g/plot), and P2 (35 g/plot). Parametersobserved were plant height, number of primary branch, flowering time, pods number per plant,filled pods number per plant, seed production per plant, seed production per plot, and weight of 100dry seeds. The results showed that only plant height 5 week after planting and pods number perplant were significantly affected by cow manure, meanwhile all parameters observed weresignificantly affected by phosphate fertilizer except for plant height and number of primary branch.There was no interaction between both treatments.Keywords : cow manure, phosphate fertilizer, peanut